NILAI-NILAI ISLAM DALAM PEMANDANGAN UMUM FRAKSI PARTAI PERSATUAN PEMBANGUNAN DAN FRAKSI PARTAI KEADILAN SEJAHTERA PADA RAPAT PARIPURNA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI SUMATERA UTARA TAHUN 2013 DITINJAU DARI PERSPEKTIF KOMUNIKASI ISLAM - ASWAN JAYA (JURNAL ILMIAH KOHESI, 2019)
Research Objectives (1) To find out the Islamic values contained in the General View of the PPP Faction and the PKS Faction which were conveyed at the Plenary Meeting of the North Sumatra Provincial Parliament throughout 2013. (2) To find out the General Views of the PPP and PKS Faction submitted. The North Sumatra DPRD Plenary Session in 2013 was reviewed from the perspective of Islamic communication. The research approach used is qualitative data analytical descriptive. Thus, this study provides an overview of Islamic Values in the General View of the PPP Faction and PKS Faction of the DPRD of North Sumatra Province in terms of the Islamic Communication Perspective. The target of the study were the texts of the General View of the PPP and PKS Faction which were read out at the North Sumatra Provincial DPRD Plenary Meeting throughout 2013. Data collection techniques used were documentation, interview techniques and library techniques. The results showed that: (1) Discussion of various state and social issues contained in the General View of the PPP and PKS Faction throughout 2013 did not fully reflect the commitment of the two political parties in upholding Islamic values. Nevertheless, there is still the content of Islamic values in the General Scripts of the PPP and PKS factions in terms of two things, first finding several words and or sentences using Islamic terms and secondly the attitudes, proposals and recommendations of the two factions still have partiality to the interests Muslims. However, the settlement approach and the inputs are still felt that both factions dissolve in the mainstream of the Plenary Meeting itself. This inconsistency with the struggle for Islamic values is one of the reasons PPP and PKS have not become the political party of choice for most Muslims in North Sumatra in particular and Indonesia in general. Understandably, in the 2014 elections, PPP and PKS dropped in gaining votes and seats in parliament. Judging from the Islamic Communication Perspective, the General View of the PPP and PKS Faction has met the ethical standards and principles of Islamic Communication itself. This is understandable because the General View was delivered in writing which was read out at a constitutional meeting namely the Plenary Meeting of the North Sumatra Provincial Parliament and subsequently became a state document. Thus, the use and arrangement of words into sentences must be well written too.